Mechanical properties of hydraulic concretes with partial replacement of Portland cement by pozzolans obtained from agro-industrial residues: A review - Ramon Torres-Ortega; Diego Torres-Sanchez; Teresa Lopez-Lara (Heliyon)
The search for alternative material sources to conventional ones has had a significant impact on the construction sector today, driven by the implementation of sustainable development policies on a global scale. Alternative cementitious materials, such as agricultural industry by-products, have been introduced to ensure the efficient use of renewable natural resources while promoting a balance between the technical and economic aspects of infrastructure projects. This article provides an overview of research conducted on the use of pozzolans derived from agro-industrial by-products, such as rice husk ash (RHA), palm oil fuel ash (POFA), and sugarcane bagasse ash (SCBA), which have a high content of amorphous silica. This silica reacts with calcium hydroxide during the hydration process of Portland cement, leading to the production of calcium silicate hydrate (C-S-H) gel with cementitious properties. Investigations have explored the improvements these pozzolans provide in terms of compressive, flexural, and tensile strength in concretes where conventional Portland cement has been partially replaced by these materials. The influence of temperature and grinding processes used in their preparation was also determined, with optimal temperatures for obtaining amorphous silica ranging between 600 °C and 700 °C. Additionally, the optimal replacement levels for enhancing the mechanical properties of concrete were found to range between 10 % and 20 %.